Quality of Life in Japanese Patients with Dysmenorrhea Treated with Ethinylestradiol 20 μg/Drospirenone 3 mg in a Real-World Setting: An Observational Study - Momoeda M; Akiyama S; Tanaka K; Suzukamo Y (Dove Medical Press, 2020)
Mikio Momoeda,1 Sayako Akiyama,2 Kota Tanaka,3 Yoshimi Suzukamo4 1Department of Integrated Women’s Health, St. Luke’s International Hospital, Tokyo, Japan; 2Market Access, Bayer Yakuhin, Ltd., Tokyo, Japan; 3Statistics Analysis Department 2, EPS Corporation, Osaka, Japan; 4Department of Physical Medicine and Rehabilitation, Tohoku University, Sendai, JapanCorrespondence: Mikio MomoedaDepartment of Integrated Women’s Health, St. Luke’s International Hospital, 9-1 Akashicho, Chuo City, Tokyo 104-8560, JapanTel +81-3-3541-5151Fax +81-3-5550-2605Email momoeda-tky@umin.ac.jpBackground: Dysmenorrhea affects approximately 80% of women in Japan and has a negative impact on health-related quality of life (HRQoL). Low-dose estrogen/progestin combined oral contraceptives have been shown to reduce the severity of dysmenorrhea symptoms. This study characterized HRQoL in Japanese women with dysmenorrhea before and after ethinylestradiol/drospirenone (EE/DRSP) treatment.Methods: This prospective, observational study recruited 531 patients, of which 186 were evaluated after treatment with EE 20 μg/DRSP 3 mg for dysmenorrhea in a 24/4 cyclic regimen. The primary endpoints were mean baseline and post-treatment 36-Item Short-Form Health Survey version 2.0 (SF-36v2) scores for study patients compared with the general female population of Japan (calculated using norm-based scoring), and mean changes in study patient SF-36v2 scores between baseline and 6 to 8 treatment cycles.Results: Compared with Japanese norms, women with dysmenorrhea had lower pre-treatment SF-36v2 scores, except for the physical functioning domain. After 6– 8 cycles of EE/DRSP treatment, all 8 SF-36v2 domain scores were significantly higher than baseline. The greatest improvements were observed in bodily pain and social functioning (mean change [standard deviation (SD)]: physical functioning: 1.4 [5.7], role physical: 3.2 [8.1], bodily pain: 7.8 [10.0], general health: 3.0 [7.0], vitality: 2.7 [8.1], social functioning: 3.5 [9.8], role emotional: 3.3 [9.2], and mental health: 3.0 [7.3]; p< 0.001 for all). Compared with the Japanese general population, study patients’ post-treatment scores were significantly higher for the general health domain (p= 0.008) and physical summary scores (p= 0.033).Conclusion: Dysmenorrhea has a profound impact on all aspects of functioning and well-being. This study, conducted in a real-world setting, found that physical, social, and mental HRQoL improved significantly after a cyclic regimen of EE/DRSP in Japanese patients with dysmenorrhea. This regimen may have the potential to provide an effective option to improve patient HRQoL.Trial Registration: Study sample was drawn from patients enrolled in a post-marketing surveillance study, registered June 20, 2011 (NCT 01375998).Keywords: patient-reported outcomes, SF-36, dysmenorrhea, quality of life, ethinylestradiol/drospirenone, Japan